Some factors affecting the reproductive performance of White Fulani (Bunaji) cattle - Oyedipe, E.O.; Buvanendran, V.; Eduvie, L.O. (1982)
An analysis of reproductive data on White Fulani (Bunaji) Zebu cattl of Northern Nigeria was carried out. The season and year of birth had no effect on age at first calving (P>0.1). The mean age at first calving was 40.4± 0.7 months. The distribution of heifers, classified according to age at first calving, appeared to be normal. Subsequent calving intervals for heifers that had their first calf in the dry and wet seasons were 458 and 540 days, respectively. The difference was highly significant (P